STUDENTS TRAINING – FUTURE TEACHERS OF EARLY SCHOOL EDUCATION FOR WORK IN CULTURALLY DIVERSIFIED ENVIRONMENT - Ogrodzka-Mazur, Ewa (The Modern Higher Education Review, 2018)
Referring to theoretical assumptions of pedagogy and intercultural education, the discussion was undertaken on their implementation by students – future teachers working with I-III class children in Cieszyn Silesia. The following issues were focused on: (1) the occurrence and role of elements of intercultural education in teaching children, (2) the range of teaching contents, (3) the implemented programmes and those in the process of preparation. The analysis was also carried out of teachers’ expert preparation and their professional training and improvement concerning the implementation of intercultural education.